DEVELOPMENT OF FLIPBOOK BASED E-MODULE LEARNING MEDIA SPA AND BEAUTY THERAPY LESSONS - Astuti, Murni; Novrita, Sri Zulfa; -, Rahmiati; Jalinus, Nizwardi; -, Ridwan (Jurnal Ipteks Terapan, 2024)
As the times progress with all the sophistication of technology, it must be utilized for progress, especially in the field of education. This research aims to develop E-Module SPA and Beauty Therapy learning media which is equipped with menus or interesting features such as learning modules, supporting images and videos, learning evaluations that can be accessed easily so that they can be used and meet the standards for validity aspects of the media and material. The research method used is the development (R&D) of a 4-D model, including the Define, Design, Develop and Disseminate stages, but in this research the Disseminate stage was not carried out because it only looked at the validity of interactive multimedia learning media. The research results show validity in validating learning media with an average of 84% in the very valid category. In material validation, results were obtained with an average of 84% in the very valid category. Based on the total results of the media and material validity assessment, it is 84%, which is included in the Valid category or very suitable for use by students in the SPA and Beauty Therapy learning process